2020
DOI: 10.1093/qje/qjaa042
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Bias of Trade Policy*

Abstract: This paper documents a new fact, then analyzes its causes and consequences: in most countries, import tariffs and non-tariff barriers are substantially lower on dirty than on clean industries, where an industry's "dirtiness" is defined as its carbon dioxide (CO 2) emissions per dollar of output. This difference in trade policy creates a global implicit subsidy to CO 2 emissions in internationally traded goods and so contributes to climate change. This global implicit subsidy to CO 2 emissions totals several hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 113 publications
2
90
1
1
Order By: Relevance
“…This growth may relate in part to domestic environmental policies (Sauvage, 2014). On the other hand, Shapiro (2020) shows that in most countries, import tariffs and non-tariff barriers are substantially lower on dirty (more upstream) than on clean (more downstream) industries. The limitation of greater protections for clean industries could help address climate change and increase welfare.…”
Section: Sustainable Tradementioning
confidence: 99%
“…This growth may relate in part to domestic environmental policies (Sauvage, 2014). On the other hand, Shapiro (2020) shows that in most countries, import tariffs and non-tariff barriers are substantially lower on dirty (more upstream) than on clean (more downstream) industries. The limitation of greater protections for clean industries could help address climate change and increase welfare.…”
Section: Sustainable Tradementioning
confidence: 99%
“…In turn, if a high tariff falls or is eliminated, carbon emissions are not shifted from countries with higher carbon taxes to countries with lower carbon taxes indicating the reduction of carbon leakage. Shapiro (2020) revealed that if countries imposed similar tariffs and non-tariff barriers to trade (NTBs) on clean and dirty industries, global CO 2 emissions would fall, while real income would not change. As the final consumers are generally not well-organized, countries end up with greater protection on clean products and less protection on polluting goods.…”
Section: Effect Of Climate Policy Measures On Trade and Economic Welfarementioning
confidence: 99%
“…When a country's participation in joint emission reduction is higher, the consumption patterns are more environmentally friendly, and welfare is much more improved (Kuhn et al 2019). Considering the welfare effects of climate policy measures, when countries impose similar tariffs and barriers on environmentally friendly and polluting industries, global CO 2 emissions tend to fall, while incomes do not change (Shapiro 2020). A nonrestrictive border carbon adjustment can lead to stable climate agreements and significant global welfare gains (Khourdajie and Finus 2020), while carbon tariffs enable global emissions reduction by altering the production within and across countries, resulting in the reduction of carbon leakage (Larch and Wanner 2017).…”
Section: Trade Liberalizationmentioning
confidence: 99%
“…Leveling the playing field by imposing similar tariffs and nontariff barriers on clean and dirty industries would have significant positive effects. Using a general equilibrium model, Shapiro (2020) postulates that if countries impose similar tariffs and nontariff barriers on clean and dirty industries, global CO 2 emissions would fall, while global real income would remain unchanged or increase slightly. Further, and with significant effects, these changes in global CO 2 emissions are of comparable scale to the estimated impacts of some of the world's largest actual or proposed climate change policies.…”
mentioning
confidence: 99%